An novel three-party authenticated key exchange protocol using one-time key - Lv, Chao (2013)
Three-party authenticated key exchange protocol (3PAKE) is an important cryptographic technique for secure communication which allows two parties to agree a new secure session key with the help of a trusted server. In this paper, we propose a new three-party authenticated key exchange protocol which aims to achieve more efficiency with the same security level of other existing 3PAKE protocols. Security analysis and formal verification using AVISPA tools show that the proposed protocol is secure against various known attacks. Comparing with other typical 3PAKE protocols, the proposed protocol is more efficient with less computation complexity.